Preparation and characterisation of polyvinyl alcohol/oil palm empty fruit bunch fibre composite - Ching, K.S.; Ealid, M.; Ching, Yern Chee; Haniff, M.; Khalid, M.; Beg, M.T.H. (Taylor & Francis, 2014)
This paper focusses on the effect of thermal ageing and mechanical properties of empty fruit bunch filled polyvinyl alcohol composites. A composite plate with various volume fractions from 0.5 to 3 wt-% of empty fruit bunch was fabricated. The composites were created by a casting evaporation technique. Generally, there appears to be intimate contact between empty fruit bunch fibre and polyvinyl alcohol. In composites with higher fibre content, there is a greater tendency for filler interaction to take place. The results showed that the addition of 1 wt-% of empty fruit bunch fibre increased the tensile strength and modulus of the polyvinyl alcohol/empty fruit bunch fibre composite. There was a further increase in the mechanical properties of all the samples after thermal ageing at 50 degrees C for 6 hours.